Study of hepatic dysfunction in type 2 diabetes mellitus accessing healthcare services in an urban tertiary care hospital - Karande, Shilpa P.; Gosavi, Santosh G.; Mishra, Chinmayee P. (International Journal of Advances in Medicine, 2017)
Background: Diabetes mellitus (DM) is an extensively researched and studied subject mainly because of two factors: its, often silent spread among the community and the wide range of complications associated with it. One of them being hepatic dysfunction, the spectrum of which ranges from clinically asymptomatic with steatosis to NASH, NAFLD, cirrhosis and rarely, hepatocellular carcinoma. Methods: This cross-sectional study was carried out in 50 patients from the general medicine OPD of a tertiary care hospital, who were selected based on certain inclusion and exclusion criteria. After clinical evaluation, routine haematological and radiological investigations in type 2 diabetic patients, mainly liver function tests, CBC, sonography of the abdomen, ECG, urine analysis, anthropometric measurements, etc were noted. Data was analyzed by using statistical package of social sciences (SPSS) version-17.0. Results: The duration of diabetes was compared with the count of USG abdomen which came positive for fatty liver. Approximately 10 (20%) patients of type 2 DM, had symptoms of dull aching pain and 7 (14%) patients had hepatomegaly on palpation, which is clinically significant. 28% of the total study group was detected having fatty liver. Prevalence studies on this study group shows that 24.14% of the patients having diabetes less than 5 years, 40% of the patients having diabetes for more than 10 years and 31.25% of patients in the duration range of 6-10 years show evidence of fatty liver on ultrasound of abdomen. Conclusions: Increased BMI, deranged blood sugar levels, early nephropathy and presence of retinopathy had significant clinical correlation with hepatic involvement in this study. There is a positive prevalence of liver dysfunction as detected on sonography of the abdomen, in patients with type 2 DM. A significant correlation was obtained between fasting blood sugar and BMI. This signifies that glycemic control management plays an important role in preventing complications of diabetes like central obesity and hepatic involvement.